ISOLATION AND STUDY OF A RECOMBINANT CARBOHYDRASE XYLANASE FROM BACILLUS LICHENIFORMIS - Kiribayeva , A.K.; Mukanov , B.A.; Baduanova, S.D.; Silayev , D.V.; Ramankulov, Ye.M; Khassenov , B.B. (Eurasian Journal of Applied Biotechnology, 2019)
Xylanases are hydrolytic enzymes involved in the degradation of xylan, the main component of plant biomass. In the present study xylanase, XynA, from Kazakh strain Bacillus licheniformis was obtained in recombinant form in Escherichia coli cells. The xynA gene was amplified from the genomic DNA of the B. licheniformis and cloned in pET-28c (+) vector under the control of the promoter of bacteriophage T7. Recombinant XynA was produced in ArcticExpressRP(DE3) cells by plasmid gene expression, protein purification was carried out by metal affinity chromatography. During the study, the dependence of the enzymatic activity of recombinant xylanase on temperature and pH was observed, it was established that xylanase has the highest activity at +50°C and pH of 6.9. The activity units at these values of temperature and pH were1859 per ml of purified protein. The working temperature and pH ranges in which xylanase conserves more than 70% activity from maximum is 40-60°C and 5-8, respectively. The data obtained are essential for the use of carbohydrase xylanase from B.licheniformis in biotechnological processes in the processing of vegetable raw materials.